Public Support for the Euro and Trust in the ECB: The first two decades of the common currency - Felix Roth; Lars Jonung (University of Hamburg, Chair of International Economics, 2019)
This paper examines the evolution of public support for the euro since its introduction as a virtual currency in 1999, using a unique set of data not available for any other currency. We focus on the role of economic factors in determining the popularity of the euro. We find that a majority of citizens support the euro in each individual member country of the euro area (EA). The economic crisis in the EA following the Great Recession led to a slight decline in public support, but the recent economic recovery has strengthened that support, which is now approaching historically high levels after two decades of its existence. We detect a similar, but less pronounced upturn in trust in the ECB during the recovery. Our econometric work demonstrates that unemployment is a key driver of support behind the euro. Given these developments, we discuss whether the large and persistent majority support enjoyed by the euro equips the currency to weather populist challenges during its third decade.
Keywords: E42; E52; E58; F33; F45; 330; Euro; public support; trust; unemployment; optimum currency area; monetary union; ECB